Prevention & Control Efforts Non-Communicable Diseases (PTM); Hypertension - Dian Wahyuni (Fakultas Kedokteran Universitas Sriwijaya, 2020)
BALITBANG KEMENKES in 2020 release data in the form of tendency of non-communicable diseases (PTM) starting from the age of 10-14 years including increasing heart pressure. The purpose of this avenue is describing the prevention and control of hypertension. The method used by the online education seminar on health cadres in Sakatiga village, FK UNSRI fostered village since 2014. Finally, it is hoped that the community (cadres) can understand and implement efforts to prevent and control hypertension in the form of routinely measuring blood pressure, taking hypertension medication regularly and using complementary therapies.